SCAMPER Based Assessment Framework to Evaluate Final Year Engineering Projects in Higher Education Institutions - Shaik, Salma; Varun, A.; Kumar, Mechiri Sandeep (Journal of Engineering Education Transformations, 2025)
With rapid technological advancements of the 21st century, there is a greater onus on the higher education institutions (HEIs) to innovate teaching methodologies. Especially, engineering education which is at the forefront of latest developments, needs to provide a stimulating and feedback-oriented learning environment to the students. The current paper presents a SCAMPER technique-based assessment framework embedded with Bloom's Taxonomy that can be used for assessing the technical feasibility, identification, and resolution of challenges for final year engineering projects. A case study is conducted utilizing the proposed framework to evaluate projects of final year Mechanical Engineering undergraduate students. Results highlighted that among the control group, 67% of students followed the traditional “modify” solution approach to a given problem whereas in the experimental group, the solution approaches were more diverse with only 35% of students choosing the “modify” approach. In terms of overall assessment scores, 70% of the experimental group scored in the upper quartile from 7 to 10 whereas for the control group, only 30% of students scored between 7 to 8 with 8 being the highest score. Based on these results, we can assert that the proposed framework enables students to a) think critically and be open to exploring different approaches to solve a problem b) justify the chosen solution approach and c) clearly explain the potential challenges and their feasible solutions. Hence, this research addresses the need to design robust frameworks that will a) guide students to think critically and to focus on novel idea generation b) facilitate instructors to thoroughly evaluate projects and to provide students with timely and comprehensive feedback. We believe that this framework is flexible enough that can be adapted to successfully evaluate student projects from diverse disciplines in higher education institutions globally.